EVEKTIVITAS PENGGUNAAN MEDIA CANVA TERHADAP PRESTASI BELAJAR IPAS SISWA DI SD MUHAMMADIYAH INTEGRATIF DUKUN - Denis Agustiyani; Ahmad Agung Yuwono Putro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the differences in student learning achievement in grade IV in the subject of science at SD Muhammadiyah Integratif Dukun and to determine the effectiveness of using Canva media on the achievement of science learning of grade IV students at SD Muhammadiyah Integratif Dukun. This study is a quantitative study with an experimental method with the research subjects of grade IV A students of SD Muhammadiyah Integratif Dukun totaling 17 students. The data collection technique for this study used observation, interviews, pre-test post-test questions and documentation. Data analysis to determine student learning achievement used quantitative descriptive analysis. The results of the analysis of the post-test test scores of the experimental class had an average value of 80.58824 while the control class had an average value of 72.9412. In conclusion, the average value of the experimental class is greater than the average value of the control class. This difference is also supported by the results of statistical tests using the Independent Sample T-Test with a Sig. value. (2-tailed) is 0.007 <0.05, therefore it can be concluded that there is a significant (real) difference in influence between the two groups and means Ho is rejected and H1 is accepted. So there is an influence and it can be said that the use of Canva media is effective on students' science learning achievement at SD Muhammadiyah Integratif Dukun.